Adherence to the Mediterranean Diet in medical students - Sonia González-Sosa; Jose Juan Ruiz-Hernández; Alicia Puente-Fernández; José María Robaina-Bordón; Alicia Conde-Martel (Cambridge University Press, 2023)
Abstract Objective: The protective effect of the Mediterranean Diet (MeDi) is undisputed. However, adherence to MeDi has decreased in recent years, particularly in young people. The aim of this study was to evaluate adherence to MeDi in medical students and to assess the influence of knowledge acquisition as well as other factors on dietary compliance. Design: A cross-sectional study was conducted on medical students. The data were obtained through anonymous surveys that collected demographic characteristics, medical history, alcohol and tobacco consumption, physical activity and adherence to MeDi - using 14-point Mediterranean Diet Adherence Score (MEDAS) -. Adherence to MeDi and related factors were evaluated by univariate and multivariable analysis. Participants: Medical students from the first to the sixth year of the 2018-2019 academic year. Setting: The study was conducted at the university of Las Palmas de Gran Canaria. Results: Of 589 respondents (73 % women) mean aged 22 years (range 18-39), 58·9 % showed good adherence to MeDi. Adherence was significantly associated with age (P = 0·017) but not with sex or the presence of comorbidities. Independently, adherence to MeDi was higher in last academic courses (OR = 2·1; 95 % CI = 1·3, 3·2; P = 0·001), in those who consumed alcohol more frequently (OR = 1·5; 95 % CI = 1·0, 2·1; P = 0·039) and in those who practiced more exercise (OR = 1·5; 95 % CI = 1·2, 1·9; P < 0·001). Conclusions: Half of all medical students did not have a good adherence to MeDi. Adherence was higher at older age in higher academic years and related to greater physical activity. It would be convenient to quantify dietary knowledge as well as implement nutritional educational programmes, favouring a healthy lifestyle.